2012
DOI: 10.1007/s11010-012-1358-z
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E slows the progression of hypercholesterolemia-induced oxidative stress in heart, liver and kidney

Abstract: Vitamin E suppresses the hypercholesterolemia-induced oxidative stress in the heart. The objectives were to investigate if: (a) hypercholesterolemia-induced oxidative stress is similar in heart, liver, and kidney, and is dependent upon duration of hypercholesterolemia; and (b) vitamin E slows the progression of oxidative stress in these organs. The rabbits were assigned to 4 groups: I, regular diet (2 months); II, 0.25 % cholesterol diet (2 months); III, 0.25 % cholesterol diet (4 months); and IV, 0.25 % chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Taken together, these findings extend our initial observations (Deci et al, 2012; Lemieux et al, 2010), recapitulate changes seen in Alzheimer’s Disease, and add to the other indices of Alzheimer’s Disease that we and others have found in the cholesterol-fed rabbit (Jiang et al, 2012; Lemieux et al, 2010; Prasanthi et al, 2010; Prasanthi et al, 2008; Woodruff-Pak, 2008; Zheng et al, 2009). As a result, the cholesterol-fed rabbit is becoming an important model for assessing mechanisms of and treatments for Alzheimer’s Disease (Chen et al, 2008; Coico and Woodruff-Pak, 2008; Jiang et al, 2012; Prasad et al, 2012; Prasanthi et al, 2010; Rojas et al, 2010; Woodruff-Pak, 2008). Elevated cholesterol causes a number of changes in brain including ventricular enlargement, blood vessel narrowing, and the deposition of beta amyloid.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Taken together, these findings extend our initial observations (Deci et al, 2012; Lemieux et al, 2010), recapitulate changes seen in Alzheimer’s Disease, and add to the other indices of Alzheimer’s Disease that we and others have found in the cholesterol-fed rabbit (Jiang et al, 2012; Lemieux et al, 2010; Prasanthi et al, 2010; Prasanthi et al, 2008; Woodruff-Pak, 2008; Zheng et al, 2009). As a result, the cholesterol-fed rabbit is becoming an important model for assessing mechanisms of and treatments for Alzheimer’s Disease (Chen et al, 2008; Coico and Woodruff-Pak, 2008; Jiang et al, 2012; Prasad et al, 2012; Prasanthi et al, 2010; Rojas et al, 2010; Woodruff-Pak, 2008). Elevated cholesterol causes a number of changes in brain including ventricular enlargement, blood vessel narrowing, and the deposition of beta amyloid.…”
Section: 0 Discussionmentioning
confidence: 99%
“…It has been found that vitamin E reduces cholesterol-related oxidation in the heart, liver and kidneys [81]. To determine the relationship between high cholesterol-induced oxidation and vitamin E supplements in the heart, liver and kidney, researchers gave high cholesterol with and without vitamin E supplement and regular diet, over two-month and four-month periods to four different groups of rabbits.…”
Section: Vitamin Ementioning
confidence: 99%
“…As for CL, researchers found that vitamin E helped to keep antioxidant reserve at control levels in the heart and increased the antioxidant reserve in the liver. Researchers concluded that vitamin E slows the progression of oxidative stress [81]. …”
Section: Vitamin Ementioning
confidence: 99%
“…There is also a growing awareness of the effects of inflammation on cognitive decline [141144]. Similarly, there are a significant number of peripheral effects of cholesterol in the rabbit that may have effects on learning and memory including atherosclerosis [145147], inflammation [5, 133, 148, 149], oxidative stress [150152], and copper [153155]. With the compromise of the rabbit's blood brain barrier that occurs with cholesterol feeding [5, 58, 156158], these peripheral effects may very well also become central effects.…”
Section: Effect Of Cholesterol and Copper On Beta Amyloid Accumulmentioning
confidence: 99%